The impact of COVID-19 pandemic response on uptake of routine immunizations and the assessment of a “catch-up” drive in the Gwalior district of Madhya Pradesh, India - Kumar, Ishant; Chaturvedi, Manish; Singh, Deeksha (International Journal Of Community Medicine And Public Health, 2022)
Background: In the year 2020, immunization services were disrupted worldwide due to COVID-19 pandemic and lockdowns. However, immunization services were soon reinstated to avoid vaccine preventable disease (VPD) outbreaks. The study was conducted to assess the impact of Covid-19 pandemic on routine immunization uptake and to assess the measures taken by the State government for the prevention of potential outbreaks; thereby suggesting measures to nullify the negative impact of COVID-19 (if any) on the immunization coverage in the district. Methods: It was a descriptive and qualitative study, conducted at two rural blocks of the Gwalior district namely Ghatigaon and Hastinapur. The one-year immunization records were analysed and healthcare workers and parents of dropout children were interviewed. Results: In Gwalior, the fully immunized child (FIC) coverage dropped to approximately 70% from an average of 90% over the last four years.Forty children were due for vaccination in April 2020 when the services were shut due to lockdown. As compared to pre-Covid lockdown period, the average number of children turning up for immunization, the enrolments of new-borns for BCG vaccination and follow-up vaccinations dropped during lockdown. The most common reason for decline was the fear of contracting COVID-19 infection. Conclusions: Immunization services should be maintained as much as COVID-19 response measures allow. Decisions related to the operation of immunization services should be taken based on a detailed assessment of the VPD epidemiology, COVID-19 transmission scenario with corresponding mitigation measures and healthcare resources.